Catalytic Behaviour Of Sulphated Zirconia Supported On Mcf As Catalyst In Selective Glycerol Esterification With Palmitic Acid To Monopalmitin - Murugan, Kishor Kumar A (Universiti Sains Malaysia, 2017)
In this study, the sulphated zirconia superacid, supported on Mesocellular Foam (MCF) was prepared by urea-hydrolysis method. Glycerol and palmitic acid was esterified in the presence of this catalysts and continuous supply of nitrogen to remove water formed. Catalyst loading and temperature of reactants was manipulated to optimize the reaction condition for the esterification. All the esterification reactions were studied in a batch process and the activity of the SZMCF catalyst under various reaction parameters such as catalyst loadings (1 – 3 wt. %) with respect to limiting reactant (palmitic acid) and reaction temperatures (160 – 180 ⁰C) was investigated. As a conclusion, SZMCF catalyst which exhibited good activity was as an active catalyst and suitable to be used in the reaction involving bulky molecules.